1996
DOI: 10.1152/ajpcell.1996.271.5.c01447
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain turnover in cultured neonatal rat heart cells: effects of [Ca2+]i and contractile activity

Abstract: Blockade of L-type Ca2+ channels in spontaneously contracting cultured neonatal rat ventricular myocytes causes contractile arrest, myofibrillar disassembly, and accelerated myofibrillar protein turnover. To determine whether myofibrillar protein turnover. To determine whether myofibrillar atrophy results indirectly from loss of mechanical signals or directly from alterations in intracellular Ca2+ concentration ([Ca2+]i), contractile activity was inhibited with verapamil (10 microM) or 2,3-butanedione monoxime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 22 publications
1
36
3
Order By: Relevance
“…Endothehal cells were pretreated with 20 |^M cytochalasin D for 3 h at 37°C. Staining the cells with FITC-conjugated phalloidin, to visualize F-actin [15,16], showed a significant disruption and degeneration of the organized microfilament network (Fig. 2B) in comparison to untreated cells ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Endothehal cells were pretreated with 20 |^M cytochalasin D for 3 h at 37°C. Staining the cells with FITC-conjugated phalloidin, to visualize F-actin [15,16], showed a significant disruption and degeneration of the organized microfilament network (Fig. 2B) in comparison to untreated cells ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The microarchitecture of the F-actin network before and after cytochalasin D treatment was visualized [15,16] by staining endothelial cells with FITC-conjugated phalloidin (160 nM, 20 min; Molecular Probes). Prior to staining, the cells were fixed (10 min, room temperature) with 2% (w/v) paraformaldehyde in sodium phosphate-buffered saline (PBS), washed (15 min) in 1% (w/v) glycine in PBS, and permeabilized (15 min) with 0.5% (v/v) Triton X-100 in PBS.…”
Section: Localization Of Cytoskeletal Microfilaments By Confocal Lasermentioning
confidence: 99%
“…Our results also showed that the presence of Clock in the cytoskeleton was dependent upon active cross-bridge cycling. Both verapamil and BDM decrease the amount of myofilaments present in myocytes but do not significantly reduce non-myofilament proteins like vimentin [21]. This further suggests that the presence of Clock in the cytoskeleton is dependent upon an active contractile apparatus rather than the filamentous cytoskeleton alone.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated that BDM not only uncouples the E-C coupling of cardiac myocytes, but also inhibits the activity of sarcolemmal L-type Ca 2+ channels (Byron et al 1996;Dooley et al 1999;Ferreira et al 1997). Thus, it was possible that the elongation of intervals of Ca 2+ oscillation was due to the BDM-induced inhibition of the activity of L-type Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 99%